2004
DOI: 10.1111/j.1523-1739.2004.00240.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Roads on the Structure of Freshwater Turtle Populations

Abstract: Road mortality has the potential to alter the structure of turtle populations because turtle populations are highly sensitive to additive sources of adult mortality. To address the issue, we captured painted turtles ( Chrysemys picta; n = 174) and snapping turtles ( Chelydra serpentina; n = 56) in 18 wetlands surrounded by low road density (≤1.5 km roads/km 2 of landscape) and 17 wetlands surrounded by high road density (>1.5 km/km 2 ) in central New York in 2002. High road density was associated with male-bia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
186
8
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 221 publications
(201 citation statements)
references
References 27 publications
6
186
8
1
Order By: Relevance
“…While T. scripta and G. geographica had a positive association with commercial areas which are tied to high vehicle density, owing to the increased availability of basking sites (Peterman and Ryan 2009;Ryan et al 2008), C. serpentina did not. In many previous studies, vehicular-based mortality rates for snapping turtles were found to be extremely high (Haxton 2000;Pettit et al 1995;Rizkalla and Swihart 2006), and vehicular mortality has been shown to adversely affect the sex ratio of turtle populations (Gibbs and Steen 2005;Steen and Gibbs 2004). Our results showed habitat use of C. serpentina negatively associated with commercial and residential areas.…”
Section: Habitat Associationssupporting
confidence: 64%
See 3 more Smart Citations
“…While T. scripta and G. geographica had a positive association with commercial areas which are tied to high vehicle density, owing to the increased availability of basking sites (Peterman and Ryan 2009;Ryan et al 2008), C. serpentina did not. In many previous studies, vehicular-based mortality rates for snapping turtles were found to be extremely high (Haxton 2000;Pettit et al 1995;Rizkalla and Swihart 2006), and vehicular mortality has been shown to adversely affect the sex ratio of turtle populations (Gibbs and Steen 2005;Steen and Gibbs 2004). Our results showed habitat use of C. serpentina negatively associated with commercial and residential areas.…”
Section: Habitat Associationssupporting
confidence: 64%
“…1; for more details regarding the study site, please see Conner et al 2005;Peterman and Ryan 2009;Ryan et al 2008and 2004 C. serpentina adults (12 female, 11 male; Table 1) were radiotracked through the majority of the active season (roughly 15 May through 30 September) and selectively during the winters to understand movement patterns and habitat use. Turtles were collected using baited 0.76-m hoop traps (Conner et al 2005).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Development of terrestrial areas could impact turtles in several ways. For example, vehicle-induced road mortality is of conservation concern to turtles (e.g., Aresco, 2005a;Gibbs and Steen, 2005;Steen and Gibbs, 2004). Where roads intersect turtle migration routes and result in high mortality, barrier walls in association with culverts facilitate safe turtle movements (Aresco, 2005b;Dodd et al, 2004).…”
Section: Discussionmentioning
confidence: 99%